Cell replacement therapy is the remedial solution for treating Parkinson’s disease - Dhivya, Venkatesan (Stem Cell Investig, 2017)
The selective degeneration of dopaminergic (DA) neurons in Parkinson’s disease (PD) has made an idol target for cell replacement therapies and other emerging surgical treatments. Certainly, by transplantation method, the therapeutic regimens such as human fetal ventral midbrain (hfVM) cells, human embryonic stem cells (hESCs), human neural stem/precursor/ progenitor cells (hNSCs/hNPCs), human mesenchymal stem cells (hMSCs), human induced neural stem cells (hiNSCs), and human induced pluripotent stem cells (hiPSCs) have been used into DA deficient striatum. In recent decades, surgical methods such as deep brain stimulation (DBS) and gene therapies have been used with the aim of treating PD. Though the technology has improved and many treating options arise, the permanent source for curing PD has not been identified yet. In this review, we examine how stem cell therapies have made advancement as a therapeutic source for PD when compared with surgical treatments.